2018
DOI: 10.1038/s41598-018-34514-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation treats Chikungunya arthralgia: a randomized controlled trial

Abstract: The Chikungunya (CHIK) virus is epidemic in Brazil, with 170,000 cases in the first half of 2016. More than 60% of patients present relapsing and remitting chronic arthralgia with debilitating pain lasting years. There are no specific therapeutic agents to treat and rehabilitee infected persons with CHIK. Persistent pain can lead to incapacitation, requiring long-term pharmacological treatment. Advances in non-pharmacological treatments are necessary to promote pain relief without side effects and to restore f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…Post-hoc comparisons were carried out using Tukey-LSD (Least Significance Difference). Partial eta-squared (η p 2 ) was reported to measure effect size and was interpreted as small (effect size >0.01), medium (effect size >0.06), or large (effect size >0.14) (26).…”
Section: Methodsmentioning
confidence: 99%
“…Post-hoc comparisons were carried out using Tukey-LSD (Least Significance Difference). Partial eta-squared (η p 2 ) was reported to measure effect size and was interpreted as small (effect size >0.01), medium (effect size >0.06), or large (effect size >0.14) (26).…”
Section: Methodsmentioning
confidence: 99%
“…For the factor block, separate comparisons were made for acquisition (first acquisition block A1 vs. final acquisition block A4), retention (A4 vs. retention block R) and transfer (A4 vs. transfer block T). Partial eta‐squared ( η 2 ) was reported to measure effect size and interpreted as small (effect size >0.01), medium (effect size >0.06), or large (effect size >0.14) [Silva‐Filho et al, ]. Post hoc comparisons were carried out using the least significance difference test ( P < 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Subsequently the guidance for pharmacological prophylaxis for a minimum of 7 days for medical inpatients who are at high risk has been challenged by haematologists both for effectiveness and cost effectiveness when the patient has been discharged before this course length has been completed. 3,4 In the last edition of Clinical Medicine, Thomas et al estimated the drug related costs of this aspect of the guidance for patients who would require ongoing prophylaxis post discharge, but they were unable to estimate the cost for district nursing support for those who could not self administer. 5 The Royal College of Physicians' Patient Safety Committee considered the implications of this element of the guidance in 2018 and concluded that the level of evidence was unclear and that implementation of the guidance across medical practice currently in the NHS did not include continuation of pharmacological prophylaxis post discharge.…”
Section: Vte Prophylaxis For Medical Patients When They Leave Hospitamentioning
confidence: 99%
“…1,2 Since chikungunya could be considered as a neglected tropical disease, potentially affecting over 1 billion people, additional supportive managements should also be investigated to establish more strategies to prevent arthralgia and increase functionality. [3][4][5] As in other rheumatic diseases, the recommended managements for chikungunya aim to prevent disability, unproductive work and secondary manifestations. [6][7][8] The chronic chikungunya arthralgia/arthritis symptoms suggests an immune mechanism to medication treatments, however the growing scientific evidences of physical rehabilitation improving functionality and quality of life should be more explored at the managements.…”
Section: Newer Rehabilitation Therapies: Strategies In Chikungunya Chmentioning
confidence: 99%
See 1 more Smart Citation